Cation‐Alloying‐Induced Blue‐Shifted and Wide‐Spectrum Polarization‐Sensitive Photodetection in Quasi‐1D SbBiS3. Issue 7 (14th July 2022) - Yang, Wen; Xiong, Tao; Liu, Yue-Yang; Yang, Juehan; Xu, Qun; Wei, Zhongming
Abstract : Polarization‐Sensitive Photodetection In article number 2200061, Juehan Yang, Qun Xu, Zhongming Wei, and co‐workers successfully obtain SbBiS3 single crystal via the chemical vapor transport method. The theoretical calculation results reveal that the band gap widening and the optical absorption blue shift of SbBiS3 are caused by cationic alloying. The cover image describes that the SbBiS3 ‐based photodetector implement a wide‐spectrum polarization‐sensitive response.